Selection of optimal intensity measures for fragility assessment of circular tunnels in soft soil deposits. Issue 145 (June 2021) - Huang, Zhong-Kai; Pitilakis, Kyriazis; Argyroudis, Sotirios; Tsinidis, Grigorios; Zhang, Dong-Mei
Abstract: This study aims to identify optimal intensity measures ( IMs ) for use in probabilistic seismic demand models (PSDMs) for circular tunnels in soft soil deposits. To this end, we performed an extended numerical parametric study involving two-dimensional time history analyses of selected soil-tunnel configurations to evaluate the response of the selected tunnels under transverse seismic shaking. A series of 18 IM s were selected and tested, corresponding to free field conditions. The selected IM s were tested on several metrics, such as correlation, efficiency, practicality, and proficiency, based on an extended number of regression analyses between the IM s and the damage measure ( DM ), for the studied tunnels. DM is defined as the ratio of the actual bending moment ( M ) to the capacitive bending moment ( M Rd ) of the tunnel lining. The results indicate that the peak ground acceleration ( PGA ) at the ground surface can be considered as the optimal IM for the shallow tunnels, whereas the peak ground velocity ( PGV ) can be considered as the optimal IM for both the moderately deep and deep tunnels. Finally, various fragility curves were constructed for the studied circular tunnels under the context of PSDMs. The findings of this study can serve as a reference for the seismic fragility analysis of circular tunnels in soft soil deposits, toward more reliable quantitative risk analysis (QRA), improved resilience, and adaptability of transportation networks. Highlights: Optimal intensity measures are proposed for circular tunnels in soft soil deposits. Fragility curves for circular tunnels in soft soil deposits are developed using optimal intensity measures. The seismic failure probability of tunnels can be readily obtained using the proposed fragility curves. The significant effect of tunnel burial depths on the selection of optimal IMs is highlighted.